EMPOWERING POWERLESS BASED ON SUFISM - Luthfi Hanifah; Annilta Manzilah Adlimah (Universitas Nahdlatul Ulama Blitar, 2022)
Rich people like to accumulate wealth without distributing it to helpless people. In fact, this is contrary to Sufism which teaches how to get closer to Allah through giving up property ownership. Interestingly, not all rich people prefer to accumulate wealth, in fact, there is economic empowerment for orphans and the needy, through infaq and alms, which are carried out by the Al-Kautsar Limpung foundation, Batang Regency, Central Java, Indonesia. This research is interested in the phenomenon of economic empowerment based on Sufism values. Therefore, the purpose of this study is to determine the economic empowerment of orphans and poor people through infaq and alms at the Al-Kautsar Foundation and the contribution of Sufism in it. This paper deals with qualitative field investigations. This paper argues that the economic empowerment of orphans and poor people through infaq and alms is carried out in the context of self-purification. Self-purification is the process of donors issuing infaq and alms as a form of asceticism, referring to three Sufi figures, namely al-Kalābāżī, al-Qusyairī, and al-Ghazzālī. This knowledge of zuhud then becomes the subconscious that accumulates, then transmits and transforms to agents in the arena of social production and continuously break through space and time.